Persistence of vaccine-elicited immune response up to 14 years post-HIV gp120-NefTat/AS01B vaccination. Issue 7 (11th February 2020) - Van Der Meeren, Olivier; Jongert, Erik; Seaton, Kelly E.; Koutsoukos, Marguerite; Aerssens, Annelies; Brackett, Caroline; Debois, Muriel; Janssens, Michel; Leroux-Roels, Geert; Mesia Vela, Doris; Sawant, Sheetal; Yates, Nicole L.; et al.
Highlights: Long-term immune response induced by the candidate gp120-NefTat/AS01B vaccine was evaluated. Antibodies binding to a HIV gp120 antigen panel persisted over 14 years post-vaccination. Persistence of antibodies binding to the V1V2 scaffold was noted 2–14 years post-vaccination. Polyfunctional gp120-specific CD4+T-cells were detected up to 14 years post-vaccination. Abstract: Background: Vaccines eliciting protective and persistent immune responses against multiple human immunodeficiency virus type 1 (HIV-1) clades are needed. This study evaluated the persistence of immune responses induced by an investigational, AS01-adjuvanted HIV-1 vaccine as long as 14 years after vaccination. Methods: This phase I, open-label, descriptive, mono-centric, extension study with a single group (NCT03368053) was conducted in adults who received ≥3 doses of the clade B gp120-NefTat/AS01B vaccine candidate 14 years earlier in a previous clinical trial (NCT00434512). Binding responses of serum antibodies targeting a panel of envelope glycoproteins, including gp120, gp140 and V1V2-scaffold antigens and representative of the antigenic diversity of HIV-1, were measured by binding antibody multiplex assay (BAMA). The gp120-specific CD4+/CD8+ T-cell responses were assessed by intracellular cytokine staining assay. Results: At Year 14, positive IgG binding antibody responses were detected in 15 out of the 16 antigens from the BAMA V1V2 breadth panel, with positive response rates ranging from 7.1% to 60.7%. The highest response rates were observed for clade B strain V1V2 antigens, with some level of binding antibodies against clade C strains. Anti-V1V2 IgG3 response magnitude breadth, which correlated with decreased risk of infection in a previous efficacy trial, was of limited amplitude. Response rates to the antigens from the gp120 and gp140 breadth panels ranged from 7.7% to 94.1% and from 15.4% to 96.2% at Year 14, respectively. Following stimulation with gp120 peptide pool, highly polyfunctional gp120-specific CD4+ T-cells persisted up to Year 14, with high frequencies of CD40L tumor necrosis factor alpha (TNF-α), CD40L interleukin-2 (IL-2), CD40L TNF-α IL-2 and CD40L interferon gamma (IFN-γ) TNF-α IL-2 CD4+ T-cells, but no CD8+ T-cells detected. Conclusions: Persistent antibodies binding to HIV-1 envelope glycoproteins, including the V1V2-scaffold, and gp120-specific cellular immunity were observed in volunteers vaccinated 14 years earlier with the gp120-NefTat/AS01B vaccine candidate.